Le Cascine di Firenze: dall’Isola alla tramvia - Leonella Pecchioli; Silvia Schiff (Ri-vista: Ricerche per la Progettazione del Paesaggio, 2015)
When Alessandro de’ Medici, Duke of the Florentine Republic, he recognized the possibility of creating a Royal Estate destined for his own use and enjoyment for agriculture and hunting, and ordered purchase of this vast area on the right bank of the Arno River. The area was outside the city walls, isolated by a dense network of canals, streams and ponds, and characterized by thick, spontaneous, riparian woodlands. Thus, in 1531 the first nucleus of the “Tenuta dell’isola” (Island Estate) was born. Today, it is the largest public park in Florence, with a total of 122 Ha, including the various sports instalments, roads, avenues and squares which alternate with large woodland areas. In 1985 an inventory was taken of the entire arboreal and shrubby vegetation of the park from a pathological, forestry and botanical point of view, following an agreement between the Municipality of Florence and the University of Florence. Based on the material and information gathered from the study, it is possible to outline a rather broad picture of the vegetative situation which can then be used to predict evolutionary trends.